264 Does the Introduction of Ward Round Stickers Improve Surgical Ward Rounds?. (12th October 2021) - Sharma, V; Fitzpatrick, E; Sharma, D
Abstract: Aim: With surgical teams in the NHS pushed to their limit under unprecedented demands, simple and effective ways for maintaining standards of patient care are necessitated. This quality improvement project aims to implement user-friendly and coherent ward round stickers as an adjunct to surgical ward rounds to deliver standardised care. Method: Baseline performance was measured against The Royal College of Surgeons of Edinburgh Surgical Ward Round Toolkit. Five recorded items were studied including: bloods, venous thromboembolism(VTE) prophylaxis, regular medications, observations, and handover to nursing staff. The surgical team was informed of the audit but not over which dates it would be conducted. In the first cycle, data was collected over a 4-week period. Ward round stickers were then implemented, and a second cycle was completed 2 months later over another 4-week period. Results: Baseline performance recorded from 74 ward round entries showed checking of bloods, VTE, regular medications, observations and handover ranged from 0% to 65%. After the introduction of ward round stickers, a second cycle was performed from 81 ward round entities. There was significant improvement from baseline with compliance in recording all five items > 85%. Conclusions: This quality improvement project showed that the use of stickers as an adjunct to surgical ward round is a simple and effective way of evidencing good practice against recommended standards.